An examination of university-school partnerships in South Africa - Mutemeri, Judith; Rajendra, Chetty (2016)
The purpose of the study was to examine university-school partnerships in the process of teacher education. The research question that guided the study was how teacher educators partner with schools in teacher training. A qualitative study was preferred because the aim was to gather information and opinions on how teacher educators trained student teachers as well as to provide a forum for pre-service student teachers to air their views about how they were trained. Twenty- six lecturers and nine student focus groups, purposively sampled, participated in the study. An - interview was used for data collection and Holliday's thematic approach was used to analyse the data. The research revealed that there was a weak partnership - between teacher education and schools. The study recommends the creation of third spaces in teacher education which involve an "equal and more dialectical relationship between academic and practitioner knowledge" in support of student teachers' learning.